The Effect of Health Banks on Share Returns in Banking Companies Listed on the IDX for the 2019 Period With Political Events (Indonesia Presidential Elections) as Dummy Variables - Roby Hadimurzani; Ardi Paminto; Irwansyah Irwansyah (Budapest International Research and Critics University, 2021)
The capital market as an economic instrument is inseparable from environmental influences, both the economic environment and the non-economic environment. Political events are one of the non-economic risks that can influence investors' decisions to invest in the capital market. The purpose of this study is to determine the effect of political events in Indonesia in 2019 on stock returns during the Campaign Period & Presidential and Vice Presidential Elections along with the election of members of the DPR, DPD, Provincial DPRD, and Regency / City DPRD until their inauguration period on listed banking company stocks. On the Indonesia Stock Exchange. With the research title